The Type III Secretion System (T3SS) of Chlamydophila psittaci Is Involved in the Host Inflammatory Response by Activating the JNK/ERK Signaling Pathway. (22nd January 2015) - He, Qing-zhi; Zeng, Huai-cai; Huang, Yan; Hu, Yan-qun; Wu, Yi-mou
Abstract : Chlamydophila psittaci ( C. psittaci ) is a human zoonotic pathogen, which could result in severe respiratory disease. In the present study, we investigated the role and mechanism of the type III secretion system (T3SS) of C. psittaci in regulating the inflammatory response in host cells. C. psittaci -infected THP-1 cells were incubated with the specific T3SS inhibitor INP0007, inhibitors of ERK, p38, or JNK, and the levels of inflammatory cytokines were analyzed using Q-PCR and ELISA. The levels of ERK, p38, and JNK phosphorylation were analyzed by Western blot. Our results verified that INP0007 inhibited chlamydial growth in vitro, but the coaddition of exogenous iron completely reversed the growth deficit. INP0007 inhibited the growth of C. psittaci and decreased the levels of IL-8, IL-6, TNF- α, and IL-1 β . Exogenous iron restored the chlamydial growth but not the production of inflammatory cytokines. These results demonstrated that the expression of inflammatory cytokines during infection was associated with the T3SS which reduced by incubation with ERK and JNK inhibitors, but not with p38 inhibitor. We concluded that the T3SS elicited inflammatory responses by activating the JNK or ERK signaling pathways in the infection of C. psittaci .